Species variation in susceptibility to the fungus Neonectria neomacrospora in the genus Abies. Issue 5 (4th July 2017) - Nielsen, Ulrik Bräuner; Xu, Jing; Nielsen, Knud Nor; Talgø, Venche; Hansen, Ole K.; Thomsen, Iben M.
ABSTRACT: The fungus Neonectria neomacrospora has recently caused an epidemic outbreak in conifer species within the genus Abies in Denmark and Norway. Christmas tree producers in Europe and North America rely, to a large extent, on Abies species. The damage caused by N. neomacrospora, including dead shoot tips, red flagging of branches and potentially dead trees, have therefore caused concern about reduced quality and loss of trees, and thereby of revenue. Field observations of natural infection of 39 taxa, from 32 species, within the genus Abies in the Hørsholm Arboretum, Denmark, were evaluated; significant differences were seen between taxa, that is, species, and between some species and their subspecies. The Greek fir, Abies cephalonica, was the only species without damage. An inoculation experiment on detached twigs with mycelium plugs from a N. neomacrospora culture showed that all species could be infected. The damage observed in the inoculation experiment could explain 30% of the variation in the field observations based on species mean values. The epidemic outbreak and the high number of species susceptible to this fungus indicate that N. neomacrospora requires attention in the cultivation and conservation of Abies species.